An Evaluation of Frankliniella occidentalis (Thysanoptera: Thripidae) and Frankliniella intonsa (Thysanoptera: Thripidae) Performance on Different Plant Leaves Based on Life History Characteristics. Issue 1 (9th February 2015) - Li, Wei-Di; Zhang, Peng-Jun; Zhang, Jing-Ming; Zhang, Zhi-Jun; Huang, Fang; Bei, Ya-Wei; Lin, Wen-Cai; Lu, Yao-Bin
Abstract : To compare the performance of Frankliniella occidentalis (Pergande) and native Frankliniella intonsa (Trybom) on cucumber and tomato leaves in laboratory, life history characters were investigated, and life tables were constructed using the method of age-stage, two-sex table life. Compared with tomato leaf, there were shorter total preoviposition period (TPOP), higher fecundity, longer female longevity, and higher intrinsic rate of increase ( r ) of both F. occidentalis and F. intonsa on cucumber leaf. Meanwhile, on cucumber leaf, the shorter TPOP, higher fecundity, longer female longevity, and higher value of r were found on population of F. intonsa but on tomato leaf which were found on population of F. occidentalis . From above, cucumber leaf was the preference to population development of both F. occidentalis and F. intonsa compared with tomato leaf. Nevertheless, on cucumber leaf, population of F. intonsa would grow faster than that of F. occidentalis, which was the opposite on tomato leaf. As to the population development in fields, much more factors would be taken into account, such as pollen, insecticide resistance, and effects of natural enemies etc.